1973
DOI: 10.1677/joe.0.0570285
|View full text |Cite
|
Sign up to set email alerts
|

The CONCENTRATION OF OESTRONE AND OESTRADIOL-17β IN SPERMATIC VENOUS BLOOD IN MAN

Abstract: SUMMARY In nine men, spermatic and peripheral venous plasma was collected at operative repair of varicocele or inguinal hernia. The concentrations (ng/100ml plasma ± s.e.m.) of both oestradiol-17β (208 ± 28) and oestrone (36 ± 5) were higher than the corresponding values in peripheral venous blood (oestradiol, 3·2 ± 0·5; oestrone, 7·4 ± 1·5). These results confirm that both oestrogens are secreted directly by the testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

1975
1975
1995
1995

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…clomiphene citrate, results in a rise in the secretion of FSH and LH (Santen, Leonard, Sherins, Gandy & Paulsen, 1971). In the rat and man, oestrogens are not only secreted by the testis (de Jong, Hey & van der Molen, 1973; Baird, Galbraith, Fraser & Newsome, 1973) but also produced by aromatization of androstenedione in other tissues such as the liver and the brain (Naftolin et al, 1975). It has been suggested that it is necessary for testosterone to be aromatized before it can exert its biological effect in many target organs including the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…clomiphene citrate, results in a rise in the secretion of FSH and LH (Santen, Leonard, Sherins, Gandy & Paulsen, 1971). In the rat and man, oestrogens are not only secreted by the testis (de Jong, Hey & van der Molen, 1973; Baird, Galbraith, Fraser & Newsome, 1973) but also produced by aromatization of androstenedione in other tissues such as the liver and the brain (Naftolin et al, 1975). It has been suggested that it is necessary for testosterone to be aromatized before it can exert its biological effect in many target organs including the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…It is known, however, that the human testis secretes E2 and a small amount of E1 (Baird et al, 1973;Doerr & Pirke, 1974;Martikainen et al, 1980). Sertoli cells also actively aromatize androgen to oestrogens following stimulation by FSH (Dorrington & Armstrong, 1975;Dorrington et al, 1978;Payne et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the direct secretion of estradiol by the human testis has been shown by Kelch et al (1972), Longcope et at. (1972, Saez et al (1972) and Baird et al (1973) on the basis of measurement of estradiol in spermatic venous blood. The castrated patients presented here revealed extremely low levels of plasma estradiol in the presence of both normal adrenal glands.…”
Section: Discussionmentioning
confidence: 99%